Molecular characterization of endocannabinoid signalling - Abdulmaqsood, Yousra (2021)
The endocannabinoid system has gained an increased focus in exploiting its therapeutic potential for the management of multiple diseases. This research aimed to investigate two components of the EC system, the EC-hydrolysing enzyme ABHD6 and signalling through CB2 receptor. Selective inhibition of ABHD6 was reported to possess anti-inflammatory and neuroprotective effects and was implicated in diverse pathological processes. Likewise, selective modulation of CB2 receptors could have a therapeutic potential in the management of inflammatory, neuropathic pain and degenerative diseases without inducing the psychoactive effects of CB1 receptor activation. This research initially aimed to develop a rapid, cost-effective, reproducible and sensitive HTS assay for screening human recombinant ABHD6. The investigated substrate 4-MUH was a promising tool for screening novel ABHD6 inhibitors. The assay also identified the potential for ABHD6 to recognise multiple endogenous lipids, which may be natural substrates of the enzyme. Nonetheless, the assay in its current configuration employed to ‘real’ tissues, of rat intestine and hippocampus, generated data that were complex and difficult to interpret. It is possible that further adapting this assay may resolve these issues.